Evaluation of the intrinsic crack growth rates of weld joints - Zhang, Xiang; Bao, Rui (Elsevier Science B.V., Amsterdam., 2011)
A method is presented for evaluating weld intrinsic fatigue crack growth rate (FCGR) by excluding the influence of residual stresses. The method is potentially useful for predicting crack growth lives of structural components using measured FCGR data from coupon specimens. Calculation procedures are developed and demonstrated via an example of crack growth across a longitudinal weld subjected to both constant amplitude loading and constant applied stress intensity factor ranges. Trends of intrinsic FCGR in different weld regions are identified. The methodology can also be used for establishing intrinsic FCGR laws for cracks propagating within and parallel with the weld joint.
Keywords: welded joints; crack growth; residual stresses; weld intrinsic property